Adapting the Boerdijk–Coxeter helix as node configuration for GPS‐denied localization in three dimensions. Issue 3 (10th September 2021) - Ann, Alvin Goh Cheng; Foong, Shaohui; Ahmed, Alvee; Soh, Gim Song
Abstract: We propose the Boerdijk–Coxeter Helix (BC Helix) model geometry as a potential node configuration for human users who are localizing within an unstructured environment. When the localization nodes are placed in Boerdijk–Coxeter Helix geometry, the nodes form a regular pattern such that the user can plant new nodes in his or her direction of travel without compromising coverage area or orientation. This paper is also a follow‐up to an earlier research paper examining algorithms for three‐dimensional localization using a barometer to assist finding the z ‐coordinate. We provide simulation results examining the potential effects of the Boerdijk–Coxeter Helix geometry on localization accuracy and computation time, and experimental results showing the potential of the helix geometry compared to the random placement of nodes.